Sex differences in the association between metabolic disorder and inflammatory cytokines in Han Chinese patients with chronic schizophrenia - Tian, Yinghan; Li, Zhenkuo; Zhang, Yun; Tang, Pei; Zhuang, Yu; Liu, Lewei; Fan, Haojie; Yao, Xianhu; Li, Wenzheng; Xia, Lei; Liu, Huanzhong (Frontiers in Psychiatry, 2025)
BackgroundPrevious evidence suggests that immune-inflammatory dysfunction plays an important role in metabolic disorder (MD) of patients with schizophrenia, yet studies on sex differences in the association between both are limited. The current study aimed to investigate sex differences in the association between MD and inflammatory cytokines in Han Chinese patients with chronic schizophrenia (CS).MethodsThis multicentre cross-sectional study was conducted in one general hospital and two psychiatric hospitals in Anhui Province, China. General information, metabolic parameters and inflammatory cytokine indicators were collected from all participants, and the severity of their psychiatric symptoms was assessed using the Positive and Negative Syndrome Scale (PANSS).ResultsA total of 324 patients completed the assessment and were included in this study. The patients with MD had higher age and duration of illness, and lower chlorpromazine equivalents and negative symptom score than those without MD. Binary logistic regression showed that MD was significantly associated with a higher IL-1β level in male patients, while this association was not significant in females. Further multiple linear regression revealed that IL-1β level was negatively correlated with polypharmacy only in male patients.ConclusionSex differences in the association between MD and IL-1β level are significant in patients with CS, and only in male patients is there a negative correlation between MD and IL-1β level. Sex-specific prevention and intervention strategies may contribute to reducing MD in patients with CS.